2000
DOI: 10.1002/1096-9071(200012)62:4<471::aid-jmv12>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

De novo infection of hepatitis B virus in patients with orthotopic liver transplantation: Analysis by determining complete sequence of the genome

Abstract: De novo infection of hepatitis B virus (HBV) occurs after liver transplantation from donors with HBV markers that suggest past infection. In the present study, the complete nucleotide sequences of HBV derived from a donor and recipients were determined to determine the clinical and virological characteristics. A total of 57 donor-recipient pairs, which underwent living-related orthotopic liver transplantation, were enrolled in the present study; all were negative for HBsAg before transplantation. HBV DNA was t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 37 publications
1
19
0
1
Order By: Relevance
“…The complete genome sequences derived from the source and the two infected patients present a small number of differences (eight and nine differences for patients 15 and 16, respectively, from a total of 3,218 nt), many of which correspond to polymorphic sites in the source that are resolved in the recipients (five cases). Similar or even higher numbers of differences (ranging from 0 to 43) have been found by full-genome comparisons between HBV isolates from source and recipient pairs in several analyses (4,7,25,32). Our statistical analyses provide strong, additional support for a link between the three full genome sequences considered in the outbreak and additional full genome sequences obtained from HBV-infected individuals from the same population.…”
Section: Discussionsupporting
confidence: 78%
“…The complete genome sequences derived from the source and the two infected patients present a small number of differences (eight and nine differences for patients 15 and 16, respectively, from a total of 3,218 nt), many of which correspond to polymorphic sites in the source that are resolved in the recipients (five cases). Similar or even higher numbers of differences (ranging from 0 to 43) have been found by full-genome comparisons between HBV isolates from source and recipient pairs in several analyses (4,7,25,32). Our statistical analyses provide strong, additional support for a link between the three full genome sequences considered in the outbreak and additional full genome sequences obtained from HBV-infected individuals from the same population.…”
Section: Discussionsupporting
confidence: 78%
“…Although clinical outcomes of a limited number of recipients of HBcAb ϩ living donor liver grafts have been reported previously, the short-and long-term safety of partial hepatectomy in HBcAb ϩ adult living liver transplant donors has not been described previously. 22,23 The majority of right-lobe liver donors in this series were women (65%), and mean donor graft weight was 574 g. The 24 HBcAb ϩ donors were significantly older than the 29 HBcAbϪ donors (median age, 42 v 31 years). Interestingly, 80% of the HBcAbϪ group were HBsAb ϩ , suggesting either previous HBV vaccination or exposure to HBV.…”
mentioning
confidence: 88%
“…It is therefore difficult to differentiate DNH from recurrent HBV infection. Such a problem can be resolved by complete sequencing of the isolated viral genome [19]. Nonetheless, anti-HBc positivity in recipients offers some protection against DNH.…”
Section: Prevalence Rate Of Anti-hbc Positivity In Lt Donorsmentioning
confidence: 99%
“…Overall, DNH rarely occurred with variable onset time in recipients positive for both serological markers. Among the 47 cases positive for both, anti-HBs and anti-HBc before LT in 10 studies, only 2 of them (4.3%) developed DNH after receiving liver allografts from anti-HBc-positive donors, even without prophylaxis (Table 1) [7,16,19,21,22,26,27,29,31,32]. Nevertheless, Takemura et al [33] reported a single case positive for both anti-HBs and anti-HBc before transplant, developing DNH at 35 months after LT.…”
Section: Prevalence Rate Of Anti-hbc Positivity In Lt Donorsmentioning
confidence: 99%